Overview of Public Knowledge and Attitudes Toward Drug Labeling on Medicine Packaging in Pasan District, Southeast Minahasa Regency - Rambi, Shekinaglory; Lolo, Widya Astuty; Jayanto, Imam (Yayasan Bina Lentera Insan, 2025)
Drug marking on drug packaging can provide complete information about the efficacy, safety, side effects, how to use, and other information included in the drug. Limited knowledge of the public about drugs and their use can cause people to lack understanding of drug information, thus allowing irrational treatment if not balanced with the provision of correct information. The purpose of this study was to determine the level of knowledge and attitudes of the community about the marking on drug packaging. This research method is descriptive with the type of survey and uses instrument in the form of a list of questions (questionnaire), with a cross sectional survey design. The sample in this study were the people of Pasan District as many as 100 samples. The results showed that 61% of respondents had a poor level of knowledge and 100% of respondents had a positive attitude. So it was concluded that the majority of people in Pasan District had a poor level of knowledge and a positive attitude about drug marking on drug packaging.